Perceived competence as a mediator in parental engagement in speech therapy - Mdshah, Nurfariha; Madon, Zainal; Ismail, Nellie (Universiti Putra Malaysia Press, 2021)
Parental engagement has been recognised as a critical factor in providing optimal speech therapy services to children. However, it continues to be challenging for clinicians to effectively engage parents in speech and language intervention for their children. Therefore, this study was conducted to investigate the roles of parental expectation and parent-therapist communication on parental engagement in speech therapy and to determine the contribution of the parent’s perceived competence as a mediator. A total of 389 respondents were selected from government hospitals in Malaysia for this cross-sectional study. Four instruments were administered: Parental Expectation Scale, Therapist-Parent Communication Questionnaire, Perceived Competence Scale, and Parent Home-programme Compliance Questionnaire. In addition, descriptive, bivariate, and mediation analyses were performed using SPSS and Smart-PLS software to address the study objectives. The results showed that perceived competence partially mediated the relationship between communication and expectation on parental engagement. Thus, it can be concluded that to ensure parental engagement in a child’s intervention which is vital for a better outcome. Parents need to be competent and believe strongly in their capabilities to practise in speech and language intervention. Moreover, policymakers and clinicians should focus on strategies that can improve parental expectations and communication.